Challenges of limited reuse and extended use of N95 filtering facepiece respirators: Lesson learnt from COVID-19 pandemic in Mumbai, India - Patel, Kinjal P; Carval, Trupti (International Journal of Occupational Safety and Health, 2021)
Introduction: Usage of personal protective equipment, which includes N95 filtering face piece respirators (FFRs), was the major preventive measure for healthcare workers to control COVID-19 transmission. However, a global shortage of N95 FFRs was observed worldwide during initial phase of pandemic. Reusing mask was the only strategy and various decontamination methods were suggested. The main objective of the study was to evaluate the compliance rate of limited reuse and extended use policy implemented in hospital. Methods: Limited reuse and extended use policy of N95 FFRs was implemented for one month in lower risk areas. Compliance to policy was checked by questionnaires asked to 100 healthcare workers verbally and challenges faced by them were noted. Results: It was observed that overall compliance to policy was 80%. Major reasons of non-compliance were suffocation, followed by smell from mask and loosened strips. Conclusion: Limited reuse and extended use method was successfully used as a bridge until sufficient N95 FFRs were not available although effective decontamination method must be established in hospitals to prepare ourselves for the future pandemics.